Reasons For the Lack of Acceptance of the New Curriculum 2021 in Bangladesh Among Teachers, Students, and Parents at The Field Level - Sayed Mahbub Hasan Amiri (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2025)
The introduction of Bangladesh’s New Curriculum 2021 a progressive shift from rote learning to competency-based education has faced significant resistance from teachers, students, and parents, undermining its potential to transform the nation’s education system. This study identifies the structural, cultural, and logistical barriers driving this resistance, including implementation gaps, urban-rural disparities, inadequate stakeholder involvement, and misaligned assessment practices. Through qualitative analysis of field-level challenges, the research reveals a critical disconnect between policy design and grassroots realities, particularly in resource-constrained rural areas. Teachers struggle with insufficient training and excessive workloads, students grapple with ambiguous evaluation criteria, and parents distrust reforms due to poor communication and financial burdens. The urban-rural divide exacerbates inequities, with rural schools lacking digital infrastructure, trained educators, and basic materials. The study underscores the urgency of collaborative reforms, emphasizing stakeholder engagement, equitable resource distribution, and alignment of assessments with higher education. By addressing these challenges, Bangladesh can bridge the gap between policy aspirations and practical execution, ensuring the curriculum fosters inclusive, future-ready learning.